Generation of monoclonal antibodies to ferret immune cell proteins in support of the ferret model to study human influenza infection - Jaedike, Alicia (My University, 2019)
Influenza is a highly contagious viral pathogen that causes respiratory illness in humans and animals. It is a major public health threat, resulting in three to five million yearly illnesses and up to 300,000 deaths worldwide. While the basic characteristics of this disease have been identified, there are still a variety of factors that remain unclear. The use of animal models to study influenza allows an accurate representation of influenza illness in humans. With animal models, there are limitations including size, maintenance costs, and clinical manifestations compared to a human infection. One of the best animal options is the ferret. Ferrets are small, have similar respiratory anatomy to humans, and can transmit influenza viruses between animals. The ability to use the ferret as a model to study influenza is hindered due to the limited availability of reagents. In order to study the immune response to influenza, reagents like monoclonal antibodies are needed. Monoclonal antibodies are useful for studying the immune response, including influenza pathogenesis, immune cell responders, and vaccine efficacy. The object of this study is to generate antibodies specific for ferret immune cell proteins to study influenza and other diseases.
Keywords: Monoclonal antibodies; Influenza; Ferrets